Analisis Yurisdiksi Pemajakan Freight Cargo Dalam Angkutan Laut Internasional Berbasiskan Klausul Shipping Pada Perjanjian Penghindaran Pajak Berganda (P3B) Di Kantor Direktorat Jenderal Pusat Tahun 2019 - Inggit Puspita Wardani; Chairil Anwar Pohan (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aimed to analyze the jurisdiction of freight cargo taxation on international sea transportation based on the shipping clause in the Double Taxation Avoidance Agreement (P3B) at the Directorate General of Taxes office in 2019. This study used a qualitative method with a descriptive approach. Data collection was carried out through interviews, observation, documentation and source triangulation. Based on the research results, the author concluded that freight cargo taxation on international sea transportation based on the shipping clause in the Double Taxation Avoidance Agreement (P3B) still largely provides taxation rights or taxation jurisdictions in the country of residence, which means that the taxation rights on freight cargo tax are dominated by the country of residence. This has resulted in lower freight cargo tax revenue in Indonesia. Especially when export activities continue to increase in the Export Value column by Main Destination Country. This only increases freight tax receipts in the country of residence. It is known that the obstacle faced in taxation jurisdictions on freight cargo is that Indonesia as a source country cannot tax export freight from the country of residence, even though taxation rights on freight have the potential to increase the state revenues. The author suggests that Indonesia propose a tax treaty renegotiation in Article 8 with the country of residence to change the taxation rights of freight cargo.